2015
DOI: 10.1039/c5ra17301a
|View full text |Cite
|
Sign up to set email alerts
|

Substituted group directed assembly of energetic lead(ii) compounds based on structure-relevant ligands

Abstract: 5-(4-pyridyl)tetrazole (Hpytz) and 5-(4-pyridyl)tetrazole-2-acetic acid (Hpytza) and their Pb(II) compounds were prepared. The substituted group not only influences the crystal structures of these coordination compounds but also the thermal behavior. The luminescence properties were investigated. The DSC tests show compound 2 can be used as potential explosive materials. For compound 2, the apparent activation energy E a , pre-exponential constant A, critical temperature of thermal explosion T b , thermodynami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Therefore, the research on tetrazole carboxylic acid complexes is of great significance ( Aromí et al, 2011 ; Fan et al, 2021 ; Liu et al, 2012 ; Sun et al, 2012 ; Huang et al, 2013 ; Li et al, 2013 ; Chen et al, 2014 ; Liu et al, 2015 ; Liu et al, 2016 ; Wu et al, 2011 ). At present, the synthesis and structure of a variety of tetrazole carboxylic acids and their coordination complexes and properties have been studied, showing their important application value in the fields of molecular magnetism, molecular absorption, and catalysis ( Wriedt et al, 2012 ; Zou et al, 2014 ; Wu et al, 2015 ; Yang et al, 2015 ; Zou et al, 2015 ). With the in-depth study of tetrazole carboxylic acid complexes, it is found that they have special biological activities against human tumor cells ( Wriedt et al, 2013 ; Li et al, 2015 ; Sun et al, 2016 ; Zhu et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the research on tetrazole carboxylic acid complexes is of great significance ( Aromí et al, 2011 ; Fan et al, 2021 ; Liu et al, 2012 ; Sun et al, 2012 ; Huang et al, 2013 ; Li et al, 2013 ; Chen et al, 2014 ; Liu et al, 2015 ; Liu et al, 2016 ; Wu et al, 2011 ). At present, the synthesis and structure of a variety of tetrazole carboxylic acids and their coordination complexes and properties have been studied, showing their important application value in the fields of molecular magnetism, molecular absorption, and catalysis ( Wriedt et al, 2012 ; Zou et al, 2014 ; Wu et al, 2015 ; Yang et al, 2015 ; Zou et al, 2015 ). With the in-depth study of tetrazole carboxylic acid complexes, it is found that they have special biological activities against human tumor cells ( Wriedt et al, 2013 ; Li et al, 2015 ; Sun et al, 2016 ; Zhu et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that coordination chemistry of this ligand is poorly explored. Only several Cu(I) [9], Cu(II) [10][11][12][13][14], Cd(II) [15][16][17][18], Mn(II) [17], Ni(II) [19], Zn(II) [9; 20-23], Pb(II) [24], Co(II) [25] complexes with coordinated 5-(4-pyridyl)tetrazolate were structurally characterised till now.…”
Section: Introductionmentioning
confidence: 99%
“…Then the 1H,1′H-[5,5′-bitetrazole]-1,1′-diol (DHBT) with additional two hydroxyl groups was designed to examine the structural modulation upon introducing oxygen chelate sites. Since lead salts are used as explosives , and additives in double-based propellants, , which is thus chosen as knot ion to construct CPs with different dimensionalities for it has different coordination preferences to nitrogen and oxygen atoms. On the basis of the above-discussed strategies, two energetic CPs 1D [Pb­(BT)­(H 2 O) 3 ] n ( 1 ) and 3D [Pb 3 (DOBT) 3 (H 2 O) 2 ] n ·(4H 2 O) n ( 2 ) have been yielded successfully.…”
Section: Introductionmentioning
confidence: 99%